Heavy metal accumulation and health risk assessment in S. alterniflora Loisel. and native plant Suaeda salsa (L.) Pall. in Dongtai Tiaozini wetland - Li, Guo; Cai, Zhenjie; Huang, Suzhen; Song, Zijie; Zhang, Yumiao; Zheng, Zheng; Luo, Ruixue; Wang, Shoubing (Frontiers in Environmental Science, 2024)
This study aims to investigate the enrichment characteristics of the dominant plant, S. alterniflora Loisel. (S. alterniflora) and Suaeda salsa (L.) Pall. (S. glauca). Regarding heavy metals, eight common heavy metal elements were selected, including Hg, Cd, Cr, As, Pb, Cu, Ni, and Zn, and examined their content in surface sediments and different parts of the two plants. The transfer characteristics of heavy metals in the plant body and their potential health risks to humans were also analyzed. These findings suggest that both plants accumulate higher concentrations of heavy metals in their below-ground parts. Cr, Cu, and Zn had the highest average concentrations in both plants.Geoaccumulation index (Igeo) indicated that the Tiaozini Wetland is not yet contaminated. S. alterniflora had transfer factors less than 1 for all heavy metals, while S. glauca had transfer factors greater than 1. Both plants had a certain purifying effect on heavy metal pollution in wetlands, including Cr, Cd, Cu, and Zn. However, Cr and As in the below-ground part of S. alterniflora and Cr in the above-ground part of S. glauca had a target hazard quotient (THQ) greater than 1, indicating a potential health risk to humans, but the carcinogenic risk is low. For other heavy metals, THQ was less than 1, indicating no health risk. The total target hazard quotient (TTHQ) of different parts of both plants was greater than 1, which must be taken into account when considering their suitability as edible resources.